Long non-coding RNA Gm10561 promotes myogenesis by sponging miR-432. Issue 13 (9th December 2022) - Wang, Shanshan; Tan, Baohua; Xiao, Liyao; Zeng, Jiekang; Zhao, Xinming; Hong, Linjun; Li, Zicong; Cai, Gengyuan; Zheng, Enqin; Gu, Ting; Wu, Zhenfang
ABSTRACT: Skeletal myogenesis is a highly ordered process finely regulated by various factors. Long non-coding RNAs play an important regulatory role in myogenesis via multiple mechanisms. In this study, we identified the lncRNA Gm10561, which was upregulated during myogenic differentiation and is highly expressed in skeletal muscle. Knockdown of Gm10561 inhibited the proliferation and differentiation of C2C12 myoblasts in vitro and muscle growth in vivo . Overexpression of Gm10561 promoted the proliferation and differentiation of both C2C12 myoblasts and porcine muscle satellite cells. Notably, lncRNA Gm10561 is localized in the cytoplasm and competitively bound to miR-432, which directly targets MEF2C and E2F3 . It was confirmed that lncRNA Gm10561 regulates the proliferation and differentiation of myoblasts by acting as a sponge of miR-432 to modulate MEF2C and E2F3 expression. Thus, the lncRNA- Gm10561 -miR-432- MEF2C / E2F3 axis plays an important role in myogenesis.